Unveiling micro-chemo-mechanical properties of C–(A)–S–H and other phases in blended-cement pastes. (May 2018) - Wilson, William; Sorelli, Luca; Tagnit-Hamou, Arezki
Abstract: Current demand for novel highly sustainable concrete urges improving the links between chemical and mechanical effects of supplementary cementitious materials (SCMs) on the microstructure of blended-cement pastes. In this work, coupled NanoIndentation and Quantitative Energy Dispersion Spectroscopy (NI-QEDS) was applied to disclose chemo-mechanical properties of microstructure phases in systems incorporating typical dosages of fly ash, slag, metakaolin, or glass powder. For a fixed water-to-binder ratio of 0.4, the C–(A)–S–H chemistry was significantly affected by the SCMs, while its average mechanical properties varied within the limited ranges M  ≈ 25–27 GPa, H  ≈ 0.7–0.8 GPa and C  ≈ 180–230 GPa. The SCMs further changed the arrangement of anhydrous phases and minor hydrates embedded in the C–(A)–S–H matrix, which were also characterized (e.g., Portlandite, AFm such as carboaluminates, or an hydrotalcite-like phase). Finally, engineering properties of blended-cement matrices requires tailoring both the intermix of hydrates and the rigid anhydrous SCM inclusions.